Imaging the presence of silane coatings in concrete with micro X-ray fluorescence. (February 2017) - Sudbrink, Bryan; Khanzadeh Moradllo, Mehdi; Hu, Qinang; Ley, M. Tyler; Davis, Jeffrey M.; Materer, Nicholas; Apblett, Allen
Abstract: Silane is a commonly used surface treatment to reduce fluid entry into the concrete matrix. This work uses micro X-ray fluorescence (μXRF) to image the presence of silane coatings in field samples and the changes made to the paste chemistry. There are many advantages that μXRF has over other imaging techniques due to the large spot size and the high energy levels. Because of this, μXRF can rapidly investigate large areas and requires minimal sample preparation. Quantitative measurements are made to show that there is a reduction in the amount of sulfur and an increase in potassium in the hydrophobic regions formed by silane coatings. These measurements provide important insights into modifications made to the concrete matrix when silane sealers are used. The mechanisms for the observed chemistry changes are discussed and a simple field or laboratory test method is presented that uses a dye to detect silane coatings.